Insertion of Norplant by midwives and physicians: A comparative cohort study - Risanto Siswosudarmo Risanto Siswosudarmo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1991)
A comparative cohort study on the insertion of Norplant by midwives and physicians had been carried out to compare its safety. A total of 500 acceptors participated in the study, 292 of which belonged to the midwive group and 202 to the physician group. They came from suburban areas surrounding the city of Yogyakarta. Although both groups were statistically differen tin terms of age and body weight, they were no t so clinically. Norplantwas delivered outside the hospital during the mass campaign (safari susuk), but standardized hospital asepsis was taken. Follow-up was done one week thereafter to detect the presence of complications or side-effects, such as pain, inflammation, abscess and sense of itching. t-test, chi-square test and relative risk were statistical analyses used in the study.Results showed that midwives inserted Norplant more rapidly compared to physicians (2.36 vs 3.45 minutes respectively), although it did not have clinical importance. 23.6% of cases among the in idwive group showed a variety of complications while that of the physician group was 19.7%, the relative risk being 1.20 (0.82-1.75). More detailed complications such as pain, inflammation, abscess and itching did not show significant difference. The risk of complication in all cases was influenced neither by the. duration of insertion nor by the level of education.The study concluded that midwives could insert Norplant as safe as physicians.Key Words: norplant-midwive-contraception-obstetrics-family planning